Immunotherapy with the trifunctional anti‐CD20 x anti‐CD3 antibody FBTA05 (Lymphomun) in paediatric high‐risk patients with recurrent CD20‐positive B cell malignancies. (11th December 2014) - Schuster, Friedhelm R.; Stanglmaier, Michael; Woessmann, Wilhelm; Winkler, Beate; Siepermann, Meinolf; Meisel, Roland; Schlegel, Paul G.; Hess, Jürgen; Lindhofer, Horst; Borkhardt, Arndt; Buhmann, Raymund
Summary: Children with B cell malignancies refractory to standard therapy are known to have a poor prognosis and very limited treatment options. Here, we report on the treatment and follow‐up of ten patients diagnosed with relapsed or refractory mature B‐cell Non Hodgkin Lymphoma (B‐NHL), Burkitt leukaemia (B‐AL) or pre B‐acute lymphoblastic leukaemia (pre B‐ALL). All children were treated with FBTA05 (now designated Lymphomun), an anti‐CD3 x anti‐CD20 trifunctional bispecific antibody (trAb) in compassionate use. Within individual treatment schedules, Lymphomun was applied (a) after allogeneic stem cell transplantation (allo‐SCT, n = 6) to induce sustained long‐term remission, or (b) stand alone prior to subsequent chemotherapy to eradicate residual disease before allo‐SCT ( n = 4). Nine of ten children displayed a clinical response: three stable diseases (SD), one partial remission (PR) and five induced or sustained complete remissions (CR). Five of these nine responders died during follow‐up. The other patients still maintain CR with a current overall survival of 874–1424 days (median: 1150 days). In conclusion, despite the dismal clinical prognosis of children refractory to standard therapy, immunotherapy with Lymphomun resulted in a favourable clinical outcome in this cohort of refractory paediatric patients.